Analysis of the System and Terrorism Attacks Prevention in an Offices of Law Enforcement Agencies in Indonesia - Warapsari Jihadtullah Tanara; Sapto Priyanto (CV. Ridwan Publisher, 2023)
Terrorism is a global issue for countries in the world, both in Indonesia itself. Since the existence of the Unitary State of the Republic of Indonesia, the country has always faced incidents and threats of terror. This study aims to determine the security system and prevention of terrorist attacks in one of the offices of law enforcement agencies in Indonesia in order to anticipate potential threats of crime that may occur. This study used a qualitative approach, followed by an analysis of the location security system based on three ring security in the surveillance detection program and CPTED (Crime Prevention Through Environmental Design). Furthermore, conclusions and anticipation of problems can be made. This study concludes that in order to create comfort and security from the threat of various criminal acts, it is deemed necessary to have an integrated security plan as a preventive measure in securing and preventing terrorist attacks at the offices of law enforcement agencies in Indonesia.